MODAL SOSIAL DALAM PENJARINGAN BAKAL CALON BUPATI DPD PARTAI GOLKAR PADA PEMILIHAN KEPALA DAERAH KABUPATEN TABANAN TAHUN 2020 - Novita Antari, Ni Kadek; Ali Azhar, Muhammad; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2020)
This study aimed to determine the selection of Turah Panji as a prospective candidate for regent promoted by the PDP of Golkar Party. Furthermore, this study was covered using the Social Capital Theory of Robert Putnam. The result of this study showed that Turah Panji was selected as the prospective candidate for regent promoted by the DPD of the Golkar Party because of the social capital he had. The types of social capital owned by Turah Panji include 1) Figure or Turah Panji's personality. 2) Family relationships and networks. 3) Track record of education and expertise possessed by Turah Panji. 4) Organization or social groups. All types of capital were put to good use by Turah Panji. Thus, he managed to attract the attention and support of the Golkar Party PDP to promote him as a prospective candidate for the regional head election of Tabanan Regency 2020.   Keywords:  Selection, Prospective Candidate for Regent, Social Capital